Béjart's Boléro, music by Ravel Maya Plisetskaya and the Ballet du XXe Siècle - Ravel, Maurice 1875-1937 (Coproduction T.R.M., 1977)
Starring the celebrated dancer Maya Plisetskaya, this brilliant performance of Boléro was given just under two decades after the 1960 premiere of what has become one of Maurice Béjart's most famous choreographies. The ballet is set to Ravel's 1928 eponymous composition, whose music is comprised of a hypnotic theme and variations: a simple repeating melody is passed among instruments in a fascinating exploration of orchestral timbres that gradually and insistently crescendos into sonic ecstasy. Mirroring this structure, Béjart's choreography places a single individual (usually a woman) at the center of a male collective that surrounds, observes, imitates, admires, and stalks her in a choreography that progressively transforms from subtle understated gestures to high-voltage electricity!
Keywords: Ballets; Webcast; Ballet films; Internet videos; Films de ballet; Vidéos sur Internet